Effects of portion size on chronic energy intake - Pentel Paul R; Levine Allen S; Harnack Lisa J; Dunn Caroline L; Rydell Sarah; Jeffery Robert W; Baxter Judith E; Walsh Ericka M (BMC, 2007)
Abstract Background This study experimentally examined the effects of repeated exposure to different meal portion sizes on energy intake. Methods Nineteen employees of a county medical center were given free box lunches for two months, one month each of 1528 and 767 average kcal. Foods were identical in the two conditions, but differed in portion size. Meals averaged 44% calories from fat. Participants self-reported how much of each lunch was eaten. Unannounced 24-hour dietary recalls were also conducted by phone twice per week during each exposure period. Results Mean energy intake at the lunch meal was 332 kcal/day higher in large lunch than in small lunch periods (p < .001). Mean 24-hour energy intake was 278 kcal/day higher in large versus small lunch periods (p < .001). There was no evidence of compensation over time. Average weight change over the month of large and small lunches was 0.64 ± 1.16 kg and 0.06 ± 1.03 kg, respectively, about what would be expected with the observed differences in energy intake. Conclusion This study suggests that chronic exposure to large portion size meals can result in sustained increases in energy intake and may contribute to body weight increases over time.